Characterization and in vitro Analysis of Probiotic-Derived Peptides Against Multi Drug Resistance Bacterial Infections - Mazumdar, Aninda; Haddad, Yazan; Sur, Vishma Pratap; Milosavljevic, Vedran; Bhowmick, Sukanya; Michalkova, Hana; Guran, Roman; Vesely, Radek; Moulick, Amitava (Frontiers in Microbiology, 2020)
An inexorable switch from antibiotics has become a major desideratum to overcome antibiotic resistance. Bacteriocin from Lactobacillus casei, a cardinal probiotic was used to design novel antibacterial peptides named as Probiotic Bacteriocin Derived and Modified (PBDM) peptides (PBDM1: YKWFAHLIKGLC and PBDM2: YKWFRHLIKKLC). The loop-shaped 3D structure of peptides was characterized in silico via molecular dynamics simulation as well as biophysically via spectroscopic methods. Thereafter, in vitro results against multidrug resistant bacterial strains and hospital samples demonstrated the strong antimicrobial activity of PBDM peptides. Further, in vivo studies with PBDM peptides showed downright recovery of balb/c mice from Vancomycin Resistant Staphylococcus aureus (VRSA) infection to its healthy condition. Thereafter, in vitro study with human epithelial cells showed no significant cytotoxic effects with high biocompatibility and good hemocompatibility. In conclusion, PBDM peptides displayed significant antibacterial activity against certain drug resistant bacteria which cause infections in human beings. Future analysis are required to unveil its mechanism of action in order to execute it as an alternative to antibiotics.